Origins and dispersal of the sweet potato and bottle gourd in Oceania : implications for prehistoric human mobility : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Clarke, Andrew Christopher (Massey University, 2009)
The origins of the sweet potato (Ipomoea batatas) and bottle gourd (Lagenaria siceraria), two important commensal species in prehistoric Polynesia, have remained elusive. Most recently, a South American origin has been favoured, which prompts a number of interesting questions surrounding how, when, from where and by whom these species dispersed into the Pacific. For this project, hypotheses were formulated based on existing archaeological, linguistic and maritime evidence, and tested using a molecular approach. For both species, extensive marker development was necessary. For the bottle gourd, a set of seven molecular markers (two chloroplast and five nuclear) was developed to test the hypothesis of a South American origin for the Polynesian bottle gourd. These were sequenced in 36 accessions of bottle gourd from Asia, the Americas and New Zealand. Analyses of these markers support a dual origin for the Polynesian bottle gourd: the chloroplast markers identify an Asian origin, but the nuclear markers reveal alleles that originate in both the Americas and Asia. By combining information from a number of sources, a model for the domestication(s) and global dispersal of the bottle gourd is proposed. For the sweet potato, the amplified fragment length polymorphism (AFLP) technique was used. First, using a new procedure that will be applicable to other studies, AFLP scoring parameters were optimised to improve phylogenetic resolution. Second, to elucidate sweet potato dispersal in Oceania, AFLP profiles were generated for 270 unique accessions of sweet potato from Asia, Island Melanesia, Polynesia and the Americas. The putative kumara lineage, which represents a prehistoric, Polynesianmediated introduction from South America, was identified. Sweet potato accessions from Asia to Western Polynesia were found to be genetically diverse, and the relationships between them are more complex than previously recognised. The phylogenetic positions of the Maori varieties ‘Hutihuti’, ‘Rekamaroa’ and ‘Taputini’ are inconsistent with these accessions representing pre-European cultivars; instead it is more likely that they are early European introductions. To answer questions about the prehistoric dispersal patterns of the bottle gourd, future work could make use of high resolution markers and ancient DNA (aDNA) from archaeological and early historic-period samples. Future work on the sweet potato is needed to narrow down the point of Polynesian contact on the South American coast, and to answer this question more intensive sampling is required. Integration of genetic, linguistic, historical and morphological data will also be important.
Content removed from thesis due to copyright restrictions: Appendix 7. Meudt, H. M. & Clarke, A. C. (2007). Almost forgotten or latest practice? AFLP applications, analyses and advances. Trends in Plant Science, 12(3), 106-117. doi:10.1016/j.tplants.2007.02.001. Appendix 8. Holland, B. R., Clarke, A. C., & Meudt, H. M. (2008). Optimizing automated AFLP scoring parameters to improve phylogenetic resolution. Systematic Biology, 57(30, 347-366. doi: 10.1080/10635150802044037. Appendix 9. Clarke, A. C., Burtenshaw, M. K., McLenachan, P. A., Erickson, D. L., & Penny, D. (2006). Reconstructing the origins and dispersall of the Polynesian bottle gourd (Lagenaria siceraria). Molecular Biology and Evolution, 23(5), 893-900. doi:10.1093/molbev/msj092. Appendix 10. Erickson, D. L., Smith, B. D., Clarke, A. C., Sandweiss, D. H. & Tuross, N. (2005). An Asian origin for a 10,000-year-old domesticated plant in the Americas. Proceedings of the National Academy of Sciences of the United States of America, 102(51), 18315-18320. doi:10.1073/pnas.0509279102.
Keywords: Lagenaria siceraria; Fields of Research::270000 Biological Sciences::270200 Genetics